CUSTOMER SATISFACTION IN TERMS OF PRODUCT QUALITY, SERVICE, BRAND IMAGE THE HARVEST CAKE SLAMET RIYADI - Rahmadani Kelana Putri; Istiatin Istiatin; Sri Hartono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The purpose of this study was to determine the effect of product quality on The Harvest Cake Slamet Riyadi customer satisfaction, the effect of service on The Harvest Cake Slamet Riyadi customer satisfaction, and the effect of brand image on The Harvest Cake Slamet Riyadi customer satisfaction. This study was carried out at The Harvest Cake Slamet Riyadi. The quantitative descriptive research design is used in this study. With 100 respondents, the population is unlimited. The sampling technique uses accidental sampling. A questionnaire is used to collect data. The statistical analysis technique utilized is the classical assumption test, multiple linear regression test, t test, and test the coefficient of determination. The findings revealed that partially product quality, service, and brand image have an impact on consumer happiness at The Harvest Cake Slamet Riyadi. The test results for the coefficient of determination obtained an Adjusted R2 value of 0.483 or 48.3%, indicating that the variables of product quality, service, and brand image influence The Harvest Cake Slamet Riyadi's customer satisfaction, while the remaining 51.7% is influenced by other variables outside of this study. Keywords: Product Quality, Service, Brand Image, Customer Satisfaction